Ethics or Moral Philosophy
VIII, 221 p.
Keywords: This volume examines a variety of philosophical approaches that seek to formulate practical guidelines or norms for human actions and behavior in different areas of society, including politics, cultural traditions, the environment, business management, architecture, and medicine. Written by a team of international authors, this volume features thirteen surveys. It begins with an exploration of ethics in politics and cultural traditions. From genocide to the unequal distribution of wealth, it examines many of the harms that currently affect societies throughout the world and considers a way that those in politics can follow to provide better care for all their populations. Next, the book looks at the relation between ethics and cultural traditions. It features a paper that examines the tension that often exists between the past and the present, with a special focus on the history of India. This volume also considers the idea of a universal system of ethics, presents a practical approach to value-based management in private and public organizations, and examines ethics in medicine. In addition, this volume includes coverage of a new type of ethics called Eco-ethica, proposed by the Japanese philosopher Tomonobu Imamichi, which seeks to answer the question of how men and women can “live better” or “live together with each other” in a systematized, technological age.